2014
DOI: 10.1128/iai.02222-14
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Anion Transporter Pendrin Contributes to Inflammatory Lung Pathology in Mouse Models of Bordetella pertussis Infection

Abstract: c Pertussis disease, characterized by severe and prolonged coughing episodes, can progress to a critical stage with pulmonary inflammation and death in young infants. However, there are currently no effective treatments for pertussis. We previously studied the role of pertussis toxin (PT), an important Bordetella pertussis virulence factor, in lung transcriptional responses to B. pertussis infection in mouse models. One of the genes most highly upregulated in a PT-dependent manner encodes an epithelial transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 58 publications
0
37
0
1
Order By: Relevance
“…More recently, Button and colleagues (52) showed that tethered mucins in the PCL form a mesh to prevent entry of gel-forming mucins and support ciliary beating, and they proposed a gel-onbrush model to describe the ASL. Photobleaching studies support this concept and have established that the fluid phase viscosity of the mucus layer and PCL are similar in non-CF subjects (7-10 times more viscous than saline), but significantly elevated in both regions in CF cultures (25)(26)(27)(28)(29)(30) times more viscous than saline) (51). In addition to forming a permeability barrier, tethered mucins in the PCL generate an osmotic pressure to regulate PCL hydration (52).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…More recently, Button and colleagues (52) showed that tethered mucins in the PCL form a mesh to prevent entry of gel-forming mucins and support ciliary beating, and they proposed a gel-onbrush model to describe the ASL. Photobleaching studies support this concept and have established that the fluid phase viscosity of the mucus layer and PCL are similar in non-CF subjects (7-10 times more viscous than saline), but significantly elevated in both regions in CF cultures (25)(26)(27)(28)(29)(30) times more viscous than saline) (51). In addition to forming a permeability barrier, tethered mucins in the PCL generate an osmotic pressure to regulate PCL hydration (52).…”
mentioning
confidence: 75%
“…Cl 2 /HCO 3 2 exchange is the relevant pendrin function in the airways during inflammatory responses (10,11,26,35). Pendrin-mediated Cl 2 /HCO 3 2 exchange was measured in pendrin-expressing FRT cells using BCECF to report cytoplasmic pH (pH i ) (Fig.…”
Section: Pendrin Inhibitors Block CLmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most recently studied novel host proteins involved in the PTX-dependent pathology induced by B. pertussis infection in mice is the epithelial anion transporter protein pendrin, indeed first identified by transcriptomic analyses. This protein was recently shown to contribute to the inflammatory lung pathology in infected mice [112]. It is likely that similar approaches will contribute in the near future to a more comprehensive view on the pathological involvement of PTX during B. pertussis infection in mice.…”
Section: Future Perspectivementioning
confidence: 97%
“…One of the genes that are most strongly upregulated in a PTX-dependent manner in the lungs of B. pertussis-infected mice codes for the epithelial anion transporter pendrin. Mice deficient for this transporter develop higher bacterial burdens, but reduced lung inflammation upon infection than pendrin-producing mice [73], suggesting that PTX triggers lung pathology via the upregulation of pendrin, which induces inflammatory responses.…”
Section: Role Of Ptx In Pathogenesis and Action On Immune Cellsmentioning
confidence: 99%